Réflexions sur la notion et l’existence d’un Art du Royaume de Majorque aux XIIIe et XIVe siècles : réalité médiévale ou construction politique du XXe siècle ? - Barral i Altet, Xavier (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić’s 70th birthday, 2020)
The Kingdom of Majorca is an entity created by the testament of James I the Conqueror, written in 1262. James divided his possessions among his sons: Peter got the County of Barcelona and the Kingdoms of Aragon and Valence. James II received the Kingdom of Majorca and the Counties of Roussillon and Cerdagne. This political construction existed between 1276 and 1344-1349. The doctoral thesis of art historian, professor at the University of Toulouse, Marcel Durliat, was published in 1962. He argued that the fourteenth-century art of the Kingdom of Majorque was independent of that of Catalonia. In this article, the author discusses this historiographical point of view.